EarlyData knowledge base for material decisions in building design. (October 2022) - Schneider-Marin, Patricia; Stocker, Tanja; Abele, Oliver; Margesin, Manuel; Staudt, Johannes; Abualdenien, Jimmy; Lang, Werner
Highlights: Fast early design LCA for non-expert users based on expert knowledge. Enriched material properties and applicability data for early design LCA. Uncertainties to account for early design vagueness. Ranges of emissions per building part and whole building. Case study for validation and illustration. Abstract: To make use of the great opportunities for emission reduction in early building design, future emissions need to be calculated when only geometric, but no detailed material information about a building is available. Currently, early design phase life cycle assessments (LCAs) are heavily reliant on assumptions of specific material choices, leading to single point emission values which suggest a precision not representative for an early design stage. By adding knowledge about possible locations and functions of materials within a building to life cycle inventory (LCI) data, the EarlyData knowledge base makes LCA data sets accessible and more transparent. Additionally, "generic building parts" are defined, which describe building parts independently of precise material choices as a combination of layers with specific functions. During evaluation, enriched LCI data and generic building parts enable assessment of a vast number of possible material combinations at once. Thus, instead of single value results for a particular material combination, ranges of results are displayed revealing the building parts with the greatest emission reduction potential. The application of the EarlyData tool is illustrated on a use case comparing a wood building and a concrete building. The database is developed with extensibility in mind, to include other criteria, such as (life cycle) costs.